Relationship between Knowledge of Pregnant Women and Compliance with Pregnancy Visits (Antenatal Care) K1 to K4 Sijambi Village, Datuk Bandar District, Uptd Work Area of Datuk Bandar Health Center 2022 - Nurhaida (Institute of Computer Science (IOCS), 2022)
The maternal mortality rate is an indicator to assess the success of achievements in maternal health efforts. One of the efforts to reduce maternal mortality is antenatal care, which is an examination of pregnancy that aims to improve the health of pregnant women, both physically and mentally optimally, and restore the health of reproductive organs. This study aims to see whether there is a relationship between knowledge of pregnant women and compliance Pregnancy Visit (Antenatal Care). This research is a non-experimental research with a descriptive correlation. The population in this study were all pregnant womenthird trimesterwho visited the Datuk Bandar Health Center UPTD, a total of 47 pregnant women. The sampling technique was carried out using the Accidental Sampling technique so that the total sample was 32 people. Data analysis used the Chi-Square test. The results of this study indicate that from the results of the knowledge questionnaire the majority of respondents had high knowledge (64.5%), while from the results of the pregnancy visit the majority were obedient (58.1%). The results of data analysis showed a value of P = 0.014, where 0.014 < 0.05. This shows that there is a relationship between knowledge of pregnant women and compliance with antenatal care K1 to K4.